Desain UI/UX pada Website PT.Serasi Media Teknologi Menggunakan Metode Design Thinking - Rianda Restu; Randi Rian Putra; Rully Dwi Arista (Jurnal Nasional Teknologi Komputer, 2025)
The purpose of this study is to apply the Design Thinking methodology to evaluate the UI/UX design on the mobile website platform of PT Serasi Media Teknologi. Effective UI/UX design can improve user experience and maximize the use of online platforms. The Design Thinking method is used to understand user needs and develop innovative solutions. It is expected that the results of this study will contribute to the development of a more effective and user-friendly mobile-based website platform. This study uses a qualitative approach by conducting observations and interviews to understand user needs. The findings of the study indicate that effective UI/UX design can improve user satisfaction and maximize the use of online platforms. This study offers recommendations for improving the UI/UX design for the mobile-based website platform of PT Serasi Media Teknologi.